ESSAI D'ADAPTATION DES MODELES DE SIMULATION DE TRAFIC URBAIN AU CONTEXTE ALGERIEN A TRAVERS DES ETUDES DE CAS - OUAZIR MANSOUR (My University, 2011)
The networks of urban traffic have become complex and jammed up. In this respect, the numerical simulation by means of developed models, especially, in the western countries, is currently the panacea to optimize the management of mentioned growing traffic. Unfortunately, the manuals of software of simulations for sale provide little or no information as to the parameters to modify according to the context in which the study is unfolding. Therefore, the user of this kind of software has a great responsibility to ensure their applicability for the conditions of local traffic. In each of these models, there are a number of parameters, which represents the characteristics of the traffic in the country where the model has been designed and calibrated. Therefore, there is a clear need for calibration and validation of the latter. Moreover, these models require very accurate data on the networks of traffic and the modes of transport. So how about the developing countries where the information is not very exact or non-existent? This study tries to apprehend the applicability of foreign simulation models for the conditions of urban traffic in Algeria. It is to identify the parameters to adapt to the context of study. And, of course, then proceed to their validation through the case studies.